2010
DOI: 10.1128/jvi.00291-10
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Airway Macrophages in Modulating Disease Severity during Influenza Virus Infection of Mice

Abstract: Airway macrophages provide a first line of host defense against a range of airborne pathogens, including influenza virus. In this study, we show that influenza viruses differ markedly in their abilities to infect murine macrophages in vitro and that infection of macrophages is nonproductive and no infectious virus is released. Virus strain BJx109 (H3N2) infected macrophages with high efficiency and was associated with mild disease following intranasal infection of mice. In contrast, virus strain PR8 (H1N1) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
255
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(280 citation statements)
references
References 71 publications
12
255
5
2
Order By: Relevance
“…In this case, virus nucleoprotein (NP) accumulated in 20 % of infected cells, but virus release was undetected [26]. Other studies support the findings of early experiments [11,[27][28][29]. However, certain seasonal H1N1 and H3N2 strains are capable of limited productive replication in mouse bone marrow-derived macrophages (BMDMs) or human MDMs, respectively [30][31][32][33].…”
Section: Replication Of Iav In Macrophagessupporting
confidence: 59%
See 1 more Smart Citation
“…In this case, virus nucleoprotein (NP) accumulated in 20 % of infected cells, but virus release was undetected [26]. Other studies support the findings of early experiments [11,[27][28][29]. However, certain seasonal H1N1 and H3N2 strains are capable of limited productive replication in mouse bone marrow-derived macrophages (BMDMs) or human MDMs, respectively [30][31][32][33].…”
Section: Replication Of Iav In Macrophagessupporting
confidence: 59%
“…Thus, the response of these cells to IAV infection is likely to be of critical importance to disease outcome. The importance of macrophages for protection against IAV infection is well established, as ablation of macrophages enhances IAV-associated immunopathology and mortality [8][9][10][11][12]. The importance of macrophages during IAV infection goes beyond protection from virus-induced pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…It is notable, however, that the apparently more permissive state of alternatively activated macrophages did not lead to production of higher levels of infectious virus than are found in classically activated cells. Although there is evidence for productive influenza virus infections in human macrophages (Hoeve et al, 2012;Perrone et al, 2008;van Riel et al, 2011;Yu et al, 2011), a number of publications have reported that influenza virus infection is abortive in murine macrophages (Rodgers & Mims, 1981;Tate et al, 2010Tate et al, , 2011. Our data show that whilst there is some replication of A/WSN/33 in murine BMDMs, the ability to produce infectious virus is not related to the activation state of the macrophage.…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies have reported that influenza viruses can infect macrophages with varying efficiency in a virus strain-dependent manner (Reading et al, 2000;Rodgers & Mims, 1981;Tate et al, 2010). We wished to investigate the ability of A/WSN/33 to infect macrophages from mice on the 129Sv/Ev background and therefore we derived macrophages from femurs of female 129Sv/Ev mice (6-8 weeks old) by culture for 7 days in medium containing macrophage colony-stimulating factor (M-CSF).…”
Section: Results 129sv/ev Bmdms Can Be Infected With Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation